ERCP with overtube-assisted enteroscopy in patients with Roux-en-Y gastric bypass anatomy: a systematic review and meta-analysis - Klair, Jagpal Singh; Jayaraj, Mahendran; Chandrasekar, Viveksandeep Thoguluva; Priyan, Harshith; Law, Joanna; Murali, Arvind R.; Singh, Dhruv; Larsen, Michael; Irani, Shayan; Kozarek, Richard; Ross, Andrew; Krishnamoorthi, Rajesh (Endoscopy, 2020)
Background Endoscopic retrograde cholangiopancreatography (ERCP) in patients with Roux-en-Y gastric bypass (RYGB) anatomy is challenging. Overtube-assisted enteroscopy (OAE) is usually needed to perform ERCP in these patients. There is significant variation in the reported rates of success and adverse events across published studies. We performed a systematic review and meta-analysis to reliably estimate the pooled rates of success and adverse events.Methods We performed a systematic search of multiple electronic databases through February 2020 to identify studies reporting outcomes of OAE-ERCP in post-RYGB patients. The pooled rates of enteroscopy success, technical success, and adverse events were estimated for OAE-ERCP. The pooled rates of success and adverse events were also estimated for ERCP using double-balloon enteroscopes (DBE) alone.Results 10 studies reporting a total of 398 procedures were included in the meta-analysis. The pooled rates of enteroscopy and technical success of OAE-ERCP were 75.3 % (95 % confidence interval [CI] 64.5 – 83.6) and 64.8 % (95 %CI 53.1 – 74.9) respectively. The pooled rate of adverse events was 8.0 % (95 %CI 5.2 – 12.2). The pooled rates of enteroscopy and technical success of DBE-ERCP (four studies) were 83.5 % (95 %CI 68.3 – 92.2) and 72.5 % (95 %CI 52.3 – 86.4), respectively. The pooled rate of adverse events with DBE-ERCP was 9.0 % (95 %CI 5.4 – 14.5). Substantial heterogeneity was noted.Conclusions OAE-ERCP appears to be effective and safe in post-RYGB patients. Among the currently available techniques, OAE-ERCP is the least invasive approach in this challenging group of patients. Future studies comparing the effectiveness and safety of alternative novel techniques, such as endosonography-directed transgastric ERCP, with OAE-ERCP are needed.